Islamic Guidance and Counseling in Developing Religious Practice Transgender - Bagas, Muhammad Ali (International Journal of Applied Guidance and Counseling, 2021)
The research aims to describe the guidance counseling Islam in developing religious practice counselees (transgender), by using research libraries in the search for sources that are relevant to the research and using content analysis as a technique for analyzing sources that exist, thus generating appropriate conclusions. The results showed that the guidance and Islamic Guidance and Counseling in developing religious practice counselees (transgender) guided by the provisions contained in it, namely; carrying out the stages, obeying and applying existing principles, to evaluating the guidance and Islamic Guidance and Counseling itself, that way, Islamic Guidance and Counseling as a development medium will be able to realize religious practice and its impact on the counselee (transgender) concerned.